Valorization of Enzymatic Hydrolysis Residues from Corncob into Lignin-Containing Cellulose Nanofibrils and Lignin Nanoparticles - Xu, Rui; Du, Haishun; Wang, Hui; Zhang, Meng; Wu, Meiyan; Liu, Chao; Yu, Guang; Zhang, Xinyu; Si, Chuanling; Choi, Sun-Eun; Li, Bin (Frontiers in Bioengineering and Biotechnology, 2021)
As a kind of biomass waste, enzymatic hydrolysis residues (EHRs) are conventionally burned or just discarded, resulting in environmental pollution and low economic benefits. In this study, EHRs of corncob residues (CCR) was used to produce high lignin-containing cellulose nanofibrils (LCNFs) and lignin nanoparticles (LNPs) through a facile approach. The LCNFs and LNPs with controllable chemical compositions and properties were produced by tuning the enzymolysis time of CCR followed by high pressure homogenization. The morphology, thermal stability, chemical and crystalline structure, as well as dispersibility of the LCNFs and LNPs were further investigated. This work not only can promote the production of lignocellulose--based nanomaterials, but also provides a promising utilization pathway for EHRs.